2021
DOI: 10.2967/jnumed.121.261894
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Static Analysis of Poly-(Adenosine Diphosphate-Ribose) Polymerase-1–Targeted 18F-Fluorthanatrace PET Images of Ovarian Cancer

Abstract: Kinetic and static analysis of poly-(adenosine diphosphate-ribose) polymerase-1 (PARP-1) targeted 18 F-FluorThanatrace ( 18 F-FTT) PET images of ovarian cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We could estimate [ 211 At]PTT SUVmax in neuroblastoma tumors to reach approximately 10, although in clinical settings SUVmax would be highly variable among different patients and even within a patient. Furthermore, we are unable to accurately estimate absorbed tumor dose from the prior [ 18 F]FTT study as the imaging window of up to 200 minutes from injection failed to reveal a washout pattern 14 . By using the biological half-life seen in mice in the present study (5.1 hr) for [ 211 At]PTT and then applying the SUVmax of 10, we can make a rough estimate of the absorbed tumor dose in a 1year-old patient to be 0.17 Gy per MBq/kg.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We could estimate [ 211 At]PTT SUVmax in neuroblastoma tumors to reach approximately 10, although in clinical settings SUVmax would be highly variable among different patients and even within a patient. Furthermore, we are unable to accurately estimate absorbed tumor dose from the prior [ 18 F]FTT study as the imaging window of up to 200 minutes from injection failed to reveal a washout pattern 14 . By using the biological half-life seen in mice in the present study (5.1 hr) for [ 211 At]PTT and then applying the SUVmax of 10, we can make a rough estimate of the absorbed tumor dose in a 1year-old patient to be 0.17 Gy per MBq/kg.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is expected that both agents would exhibit similar kinetics in vivo. In ovarian cancer patients, [ 18 F]FTT displayed rapid tumor uptake kinetics between 60-180 minutes post injection with minimal wash-out 14 . Considering [ 18 F]FTT as a surrogate for PARPi, We envisioned the rapid tumor targeting kinetics, slow target off-rate, and deep tumor penetration of a small molecule PARPi to be perfectly matched for the half-life of 211 At (7.2 h).…”
mentioning
confidence: 99%
“…Its performance compared to screening for BRCA1/2 mutations in predicting and selecting patients for PARP inhibitor therapy warrants further evaluation [ 63 ]. Young et al studied the pharmacokinetics of [ 18 F]FTT and concluded that imaging at 60 min post-injection is optimal, and whole-body SUV is a robust metric for noninvasively quantifying PARP1 expression in vivo [ 73 ]. McDonald et al conducted a two-single-arm prospective non-randomized clinical trial evaluating PARP expression in breast cancer [ 74 ].…”
Section: [ 18 F]f-radiolabeled Molecular Probes Fo...mentioning
confidence: 99%
“…PET images from this study showed visible [ 18 F]FTT uptake in tumor regions from one out five patients with measurable tumors who had a biphenotypic hepatocellular carcinoma/cholangiocarcinoma [ 82 ]. An erratum to the study corrected that a patient with pancreatic ductal adenocarcinoma, who was originally reported to show [ 18 F]FTT uptake, did not demonstrate [ 18 F]FTT uptake above the background activity [ 83 ]. The effective dose was estimated at 6.9 mSv, which is in a similar range of a [ 18 F]FDG PET scan.…”
Section: Clinical Evaluation Of Parp Imaging Agentsmentioning
confidence: 99%